Chilean Virtual Observatory - Parada-Daza, V (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents the challenges, architecture and current status of the Chilean Virtual Observatory (ChiVO), which is a software infrastructure for accessing and processing astronomical data generated in Chile. As ChiVO is part of the International Virtual Observatory Alliance (IVOA), we strictly follow the protocols and standards that this organization produce. However, there are always open challenges due to the new observational technologies and local requirements that motivates research on every new virtual observatory, such as the complex data models and Big Data problems that the ALMA Observatory is confronting. The current ChiVO prototype includes IVOA compliant services as well as new solutions designed for ALMA data, all of them using modern software technologies. © 2015 IEEE.